Solid-phase microextraction for determining twelve orange flavour compounds in a model beverage emulsion - Mirhosseini, H; Tan, CP; Yusof, S; Hamid, NSA (John Wiley & Sons Ltd, 2024)
Indexed by WOS/ Scopus